Fluid dynamic study of mixtures of sugarcane bagasse and sand particles: Minimum fluidization velocity - Pérez, Nestor Proenza; Pedroso, Daniel Travieso [UNESP]; Machin, Einara Blanco [UNESP]; Antunes, Julio Santana [UNESP]; Verdú Ramos, Ricardo Alan [UNESP]; Silveira, Jose Luz [UNESP] (Elsevier, 2017)
This paper is focused on the study of fluid-dynamic behavior of mixtures of the sugarcane bagasse particles and quartz sand in a transparent fluidized bed column. The minimum fluidization velocity (Vmf) was determined by different mean particle diameters and different mass fractions in the mixture compositions. The values of Vmf increased with amount of biomass in the mixture increased as well as with the size of the biomass particles in the range of 9.5 ≥ dpb > 0.225 mm. Binary mixtures with diameter ratios biomass/sand ≤1 had a (Vmf) almost constant as a function of mass fraction of biomass. It is suggested a practical upper limit of biomass fraction in the mixtures less than 5% of the overall bed mass to obtain a good mixing and uniform distribution in the bed. New correlations were developed to predict the values of (Vmf). It was found that the present proposed correlation predicted the (Vmf) for binary mixtures of sugarcane bagasse and sand particles more accurately than other correlations reported in the literature available.
Keywords: Biomass sand mixture; Fluidized bed; Minimum fluidization velocity; Segregation